2009
DOI: 10.1002/chem.200901245
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity Dependency on Catalyst Components in Aerobic Copper–TEMPO Oxidation

Abstract: The influence of catalyst components in the copper–TEMPO (2,2,6,6‐tetramethylpiperidine N‐oxide) catalysed aerobic oxidation of alcohols was investigated. The type and amount of base greatly influences reactivity. The bipyridyl ligand concentration had no major influence on catalysis, but excessive amounts led to a decrease in activity for longer reaction times. The kinetic dependency for TEMPO was found to be 1.15, and for copper 2.25, which is an indication of a binuclear catalytic system. Optimised conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
176
2
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(186 citation statements)
references
References 125 publications
4
176
2
4
Order By: Relevance
“…However, further studies are needed to elucidate the mechanism in more detail and with greater accuracy. Especially in light of recent studies concerning alcohol oxidation using CuBr 2 /bipyridine/TEMPO and mechanistic insights therein, 24 we cannot exclude a bimetallic catalytic mechanism at this stage.…”
Section: Resultsmentioning
confidence: 92%
“…However, further studies are needed to elucidate the mechanism in more detail and with greater accuracy. Especially in light of recent studies concerning alcohol oxidation using CuBr 2 /bipyridine/TEMPO and mechanistic insights therein, 24 we cannot exclude a bimetallic catalytic mechanism at this stage.…”
Section: Resultsmentioning
confidence: 92%
“…Although monometallic mechanisms dominate this field, there is some precedent for highly active bimetallic species [61]. Recently, a kinetic dependency for copper of 2.25 was identified for Cu-bipyridine/TEMPO complexes in aerobic alcohol oxidation reactions [41]. Also, it should be noted that given the differences in reactivity observed for our catalyst system compared with those in the literature (Table 5), Cu-L1 is likely to perform such oxidation reactions via a different mechanism compared with bipyridine-derived systems.…”
Section: Preliminary Mechanistic Insightsmentioning
confidence: 99%
“…Repo et al recently reported a highly efficient catalytic system based on TEMPO/Copper diimine (10 bar oxygen) and 2-Narylpyrrolecarbaldimino (1 atm oxygen) systems for alcohol oxidation [39][40]. In recent studies, Koskinen et al and Stahl et al have described improved bipyridine-Cu-TEMPO catalytic systems for the effective oxidation of alcohols [41][42]. In both of these studies, trifluoromethanesulfonate copper salts were found to afford greater activity compared with copper halides, and use of Nmethyl-imidazole as the base was advantageous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] For the latter system, numerous improvements have been reported since the pioneering work of Semmelhack et al that used Cu(I)/TEMPO in DMF. [5] Sheldon et al found the accelerating effect of 2,2'-bipyridine (bpy) ligands on the Cu(II) catalytic system, [6] Koskinen et al optimized the type and amount of base with Cu(II), [7] and Stahl et al performed scope and limitation studies as well as kinetic and mechanistic investigations demonstrating the importance of Cu(I) salts and N-methyl-A C H T U N G T R E N N U N G imidazole (NMI) as base. [8][9][10][11] The applicability of the system has been expanded to prepare nitriles from aldehydes or alcohols using aqueous ammonia [12] or to oxidize amine [13] and amino alcohols [14] into imines and amino carbonyl compounds, respectively.…”
mentioning
confidence: 99%